Cover Picture: Z500017 (ChemNanoMat 2/2015). Issue 2 (August 2015) - Saito, Yuta; Higuchi, Takeshi; Sugimori, Hidekazu; Yabu, Hiroshi
Abstract : A new facile method for direct synthesis of metal phthalocyanine nanocrystals from their precursors is reported in the Communication onpage 92 by Takeshi Higuchi, Hiroshi Yabu, and co‐workers. This method is based on a chemical reaction in nanosized micelles under UV irradiation. The aqueous dispersions of metal phthalocyanine nanocrystals showed strong visible light absorption from 500 to 800 nm and high transparency at wavelengths in the non‐absorption region. This method is universally applicable to prepare various metal phthalocyanines.